2018
DOI: 10.1186/s12872-018-0785-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between admission anemia and long-term mortality in patients with acute myocardial infarction: results from the MONICA/KORA myocardial infarction registry

Abstract: BackgroundPrevious studies have shown that the presence of anemia is associated with increased short- and long-term outcomes in patients with acute myocardial infarction (AMI). This study aims at examining the impact of admission anemia on long-term, all-cause mortality following AMI in patients recruited from a population-based registry. Contrary to most prior studies, we distinguished between patients with mild and moderate to severe anemia.MethodsThis prospective study was conducted in 2011 patients consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
4
13
1
2
Order By: Relevance
“…In addition, patients with anemia are more likely to have worse outcomes and higher mortality when these complications occur. 6 , 26 The increase in risk of postoperative acute myocardial infarction and cardiac arrest has been noted in other studies. A study by Oldeji et al 20 found a similar relationship between presurgery anemia and the risk of myocardial infarction after TSA with an OR of 1.62.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, patients with anemia are more likely to have worse outcomes and higher mortality when these complications occur. 6 , 26 The increase in risk of postoperative acute myocardial infarction and cardiac arrest has been noted in other studies. A study by Oldeji et al 20 found a similar relationship between presurgery anemia and the risk of myocardial infarction after TSA with an OR of 1.62.…”
Section: Discussionmentioning
confidence: 56%
“…Consistent with that finding, previous studies showed that the presence and severity of anemia was adversely associated with shortand long-term mortality risk. [13][14][15] Compared with the gen-…”
Section: Risk Factorsmentioning
confidence: 99%
“…Anemia following acute myocardial infarction (AMI) is associated with poorer outcomes relative to nonanemic AMI patients. Furthermore, anemia is more frequently encountered in patients hospitalized for cardiac events than in the general population [1,2], ranging from 11% to 38% in patients with AMI [3,4].…”
Section: Introductionmentioning
confidence: 99%